An analysis of the effectiveness of marketing and public relations strategies on company promotions: a case Study of Daily Star Digital sector - Mahim, Mahia Sunnah (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.